Modeling the Distribution and Environmental Preferences of the Ladakh Urial in the Arid Himalayas - Jeremy Roy Lambe; Mohd Raza; Tsewang Namgail (Ecology and Evolution)
ABSTRACT Mountains play a crucial role in shaping the climate of an area and subsequently, the environments and species that are suited to those particular conditions. Understanding the relationships between environmental conditions and their influence on the occurrence of a species is necessary to make informed decisions when conserving relevant habitats. This study evaluated and compared the potential for different interactions between climatic variables to describe the environmental preferences and the range of the Ladakh urial, a narrowly distributed sub‐species of Ovis vignei, in the arid Himalayas. Species distribution models were created from spatially thinned presence‐only occurrence data of 50 locations using a Maximum Entropy (Maxent) model. For this, we subdivided the modeled distribution into environmental categories with varying degrees of suitability. We identified a high cold precipitation to annual precipitation ratio typical of cold desert climates well suited to describe the highest quality environments for urial. The inverse, low warm precipitation to annual precipitation ratio was found to better describe the urial's range at the lower end of potential habitat. In this comparison, we observed that with the exclusion of unsuitable cold steppe habitat with a higher warm precipitation to annual precipitation ratio, we were able to refine the extent of this species range but at a trade‐off to the accurate description of high‐quality environments. This study demonstrated the strong potential of cold arid climatic conditions to describe the distribution of urial in India, which have implications for identifying important areas for the conservation and management of the species in the high altitude rangelands of Ladakh.